Voltage Dips Simulation In Distribution Systems In Malacca Malaysia - Omar, Rosli; Sulaiman , Marizan (2005)
The objective of this paper is to present the voltage dips simulation in distribution systems in Malacca, Malaysia. A case study is carried out on load behaviour during voltage dips in distribution system. In this paper most of the work is focused on the voltage dip due to single line to ground faults, three phase to ground faults and induction motor starting. Understanding significant characteristic of voltage dip is important before mitigation issues can be dealt with. Subsequently correct mitigation techniques are proposed. The simulation results were performed in distribution system using PSCAD/EMTDC software.